Personal Description in “Almost Heaven by Judith Mc Naught and “Days Gone By’’ By Abdulla Kadiri (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the contrasting approaches to character development in Judith McNaught's Regency romance, "Almost Heaven," and Abdulla Kadiri's historical novel, "Days Gone By." While McNaught employs archetypal characters and focuses on romantic relationships within the confines of societal expectations, Kadiri delves into the complexities of Uzbek society during a period of social change, presenting characters grappling with tradition, modernization, and political upheaval. By analyzing the distinct styles of characterization, description, and dialogue, the article highlights the influence of cultural context and genre conventions on literary representations of human experience. Ultimately, the comparison reveals the diverse ways authors utilize characters to explore themes, construct narratives, and reflect upon the social and cultural landscapes of their respective works.